Ecological patterns of seed microbiome diversity, transmission, and assembly. (June 2017) - Shade, Ashley; Jacques, Marie-Agnès; Barret, Matthieu
Highlights: Seeds harbor numerous micro-organisms, collectively referred to as microbiota. The composition of the seed microbiota can impact seed quality and ultimately plant fitness. Seed-associated micro-organisms could be vertically or horizontally inherited depending on their transmissions pathways. Niche and neutral processes are both involved in the assembly of the seed microbiota. Abstract : Seeds are involved in the transmission of microorganisms from one plant generation to another and consequently act as the initial inoculum for the plant microbiota. The purpose of this mini-review is to provide an overview of current knowledge on the diversity, structure and role of the seed microbiota. The relative importance of the mode of transmission (vertical vs horizontal) of the microbial entities composing the seed microbiota as well as the potential connections existing between seed and other plant habitats such as the anthosphere and the spermosphere is discussed. Finally the governing processes (niche vs neutral) involved in the assembly and the dynamics of the seed microbiota are examined.